Advances in research on noble gas as tracers of geofluids and helium enrichment - Yu GAO; Quanyou LIU; Dongya ZHU; Xiaoqi WU; Pengpeng LI (Meitian dizhi yu kantan, 2025)
BackgroundNoble gases emerge as significant tools for tracing the sources and evolutionary processes of geofluids due to their chemical inertness and different isotopic compositions across varying reservoirs. Helium serves as a noble gas tracer and a scarce resource, and its enrichment mechanisms and exploration potential have attracted wide attention.MethodsBased on a summary of the geochemical data of typical gas reservoirs, volcanic gases, and surface hot springs at home and abroad, this study analyzed the interfering factors and end-member value screening in the source apportionment of noble gases. Furthermore, it summarized the applications of noble gas isotopes in multiple scenarios such as constructing reservoir models and reconstructing fluid distribution. Accordingly, the helium accumulation theory was generalized based on the generation potential of helium, as well as its migration and accumulation mechanisms.Advances and Prospects By combining case studies, this study proposed three helium enrichment types: tectonic activity enhancing helium flux type (e.g., the Lhasa Block in the Qinghai-Tibet Plateau), the self-sealing-based helium accumulation in deeply buried high-pressure shale (e.g., the Cambrian and Silurian shale gas reservoirs in the Sichuan Basin), and helium accumulation based on the coupling of alkane gases and the precipitation of helium dissolved in water (e.g., the Hetianhe gas field in the Tarim Basin). The crust-derived helium flux in the Lhasa block shows a theoretical value 221 to 78 056 times the global average, with numerical simulations yielding 6 392 to 9 284 times, establishing this block as an ideal region for helium accumulation. Since the high-pressure nanopore system can significantly inhibit helium diffusion and an earlier hydrocarbon generation peak corresponds to a prolonged sustained helium enrichment stage, this study posits that the deeply buried ancient shale gas reservoirs possess ideal conditions for helium accumulation. Additionally, when the alkane gases accumulating in the late stage migrated toward traps, they can extract helium from widespread ancient formation water, leading to helium enrichment. Therefore, it is considered that these reservoirs also represent an ideal helium accumulation type.